THE CHALLENGES AND DIFFICULTIES OF BLACK LEADERSHIP IN THE LABOR MARKET - Blanc, Adriana Isabela Luciana; de Souza, Elisângela Gonzaga; da Costa, Elvio Carlos (Revista Interface Tecnológica, 2023)
This article highlights the social inequality experienced by black people in society and in the labor market. Over the years, such inequalities remained, aggravating discrimination and racial prejudice. To understand this trajectory, it was necessary to understand the submission, the search for inclusion and qualification for the job market. Therefore, the general objective of this work was to identify the challenges that black leaders face with racism. The methodology used was a bibliographic and field research through the application of a Google Forms questionnaire, consisting of 8 questions and applied to 72 participants who work as employees of companies from different segments, such as: commercial, administrative, financial, educational, among others, from the city of Araraquara - SP. The result shows that the majority of respondents understand the definition of racism, as well as having been victims of such prejudice. In addition, a significant percentage of participants believe in the importance of teaching as a way to combat racism, but few support affirmative actions for inclusion of blacks. Therefore, the development of this study highlights the importance of structural changes in order to promote inclusion and equality among people, regardless of race or any other social marker.